Self-Guiding Backscattering Immune Transportation of Light in the Visible Range - Qiuyue Zhang; Xun Li (IEEE Photonics Journal, 2019)
The implementation of topological photonic systems at optical frequency is of great significance for practical applications. In this work, we extend the study of unidirectional transmission to the visible light range with a relatively simple structure. We theoretically demonstrated the existence of self-guiding one-way edge modes at the interface between air and a hexagonal lattice of rods with a layered plasmo-semiconductor-gyroelectric metamaterial as the background medium. The inherent loss in metals can be compensated by the incorporation of the semiconductor layers with optical gain. Our simulation result shows that the self-guiding transmission remains 82% over a distance of about 30 wavelengths. In addition, it renders the light travel on such an interface insensitive to obstacles or impurities either on-purposely introduced or caused by manufacturing imperfections or variations. We show that the power transmission remains around 80% even in the presence of deliberately introduced obstacles. By exploiting the robust self-guiding unidirectional transport feature, we have designed a shape-independent cavity that can tolerate sharp corners in different angles, which eliminates the reflection and relaxes the geometrical constraint in design of integrated photonic devices.